2019
DOI: 10.1111/pan.13752
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ketamine on emergence agitation in children: A systematic review and meta‐analysis

Abstract: Background: Ketamine is believed to reduce the incidence of emergence agitation in children undergoing surgery or procedure. However, recent randomized controlled trials reported conflicting findings. Aims:To investigate the effect of ketamine on emergence agitation in children. Methods: Databases of MEDLINE, EMBASE, and CENTRAL were systematically searched from their start date until February 2019. Randomized controlled trials comparing intravenous ketamine and placebo in children were sought. The primary out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
(101 reference statements)
0
16
0
Order By: Relevance
“…Some studies have reported the pharmacological strategies to prevent EA or ED, including midazolam, propofol, ketamine, opioids, and α 2 adrenergic receptor agonists (5)(6)(7)(8). Activation of an α 2 adrenergic receptor can contribute to pharmacological effects of sedation, analgesia, and anti-inflammation; thus, an α 2 adrenergic receptor may be a target for prevention and treatment of EA or ED (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported the pharmacological strategies to prevent EA or ED, including midazolam, propofol, ketamine, opioids, and α 2 adrenergic receptor agonists (5)(6)(7)(8). Activation of an α 2 adrenergic receptor can contribute to pharmacological effects of sedation, analgesia, and anti-inflammation; thus, an α 2 adrenergic receptor may be a target for prevention and treatment of EA or ED (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis concluded that dexmedetomidine significantly decreased the incidence of post-anesthesia EA in pediatric patients compared with placebo, midazolam, and opioids [ 23 ]. Similarly, Ng et al [ 24 ] also demonstrated the efficacy of ketamine in reducing EA in children undergoing surgery.…”
Section: Discussionmentioning
confidence: 91%
“…The results of the evaluation of 13 randomized controlled trials (1125 patients) comparing intravenous ketamine in addition to inhalational anesthetics versus placebo for preventing EA in children yielded that the incidence of EA was 14.7% in the ketamine group and 33.3% in the placebo group. Being statistically insignificant, it was stated that it is difficult to claim that ketamine is a postoperative EA inhibitor [19].…”
Section: Discussionmentioning
confidence: 99%